The Problem of Law-Abiding Behavior among Minors in Educational Institutions: Domestic and Foreign Experience - Salakhova, Valentina B. (2020)
At present, the problem of sustaining the law-abiding behavior of minors in educational institutions, identifying and eliminating the causes and conditions that contribute to the development of deviant behavior of students is becoming more and more topical. This paper presents the results of a monitoring study of the current state of the activities carried out by educational institutions to form the law-abiding behavior of minors in the territorial entities of the Russian Federation. It also presents the results of a theoretical study of the foreign experience of educational institutions in the framework of maintaining the law-abiding behavior of minors in the educational environment. The conclusions have been drawn that a system-activity approach should be the basis of an educational impact in educational institutions which will provide: the formation of students’ readiness for self-development; the design and construction of a social environment for the development of students based on moral principles, traditional Russian values, relevant scientific knowledge and skills, respect for the traditions of the multinational, multicultural and multiconfessional Russian society; active educational and cognitive activities of students; building educational and moral education activity, taking account of the individual age-related psychological and physiological characteristics of students and with a focus on educational results. The materials of the paper are part of a large-scale study within the framework of the "Conception for the development of a system for the prevention of neglect and juvenile delinquency for the period up to 2020", conducted by a team of scientists from 2017 to 2020, whose scientific interests lie in the study of the problem of deviant behavior of minors.